Serving customers. - 4 0 16; 5 (Australia : Video Education Australasia)
Using practical skill demonstrations, role-plays, computer graphics and descriptive narration, this series explains the many skills, competencies and personal attributes needed to gain employment in the hospitality sector. This series is an essential resource for every Australian TAFE College and RTO delivering courses in tourism and hospitality, especially Certificate IV in Hospitality (Food & Beverage Service); and an invaluable resource for VET students studying hospitality units. This episode covers Greeting & Seating Guests, Ordering Drinks and Ordering Food.
DVD format.
Keywords: 2 -- 0; 6; Customer relations.;Hospitality industry. -- 20; 20; 2